Extrato de algas marinhas no crescimento de bananeira cv. Prata-Anã na fase de aclimatização - Brant, Luciana Alves Caldeira (2016)
Banana is the most cultivated tropical fruit in the country, but faces some limitations to its expansion mainly due to the use of seedlings produced by conventional methods that provide low multiplication rate, as well as being a source of spread of disease and pests. Faced with this problem, micropropagation is an alternative offering high quality plant seedlings in larger quantities among other benefits. In micropropagation, all steps have great participation in the final quality of the seedlings example of acclimatization in which the seedlings need nutrients and favorable conditions for its good adaptation to the external environment. Marines seaweeds have been increasingly studied as biofertilizers and biostimulants plants providing more nutrition and quality of fruit seedlings. In addition, marine seaweeds are potential alternatives in agriculture to reduce the overuse of fertilizers and other products that cause great environmental impact. The aim was to investigate the effect of different seaweeds and concentrations in acclimatization process of banana cv. Prata-Anã. The plant material consisted of micropropagated banana plantlets. Three seaweed extracts were tested (Hypnea, Lithothamnium and Sargassum) at four concentrations (0, 3.0, 6.0 and 12.0 mL L-1). After 120 days of acclimatization in the greenhouse, phytotechnical, physiological, anatomical and nutritional were evaluations. The experimental design was randomized blocks in a factorial 3x4 (three seaweeds and four concentrations) with four repetitions, each repetition represented by three plants. Among the variables studied in the reviews, it was found that 6 mL L-1 Lithothamnium provided a greater increase in banana seedlings cv. Prata-Anã adaptation of seedlings acclimatization since showed an increase in the aerial part, higher photosynthetic activity, good nutrient content in relation to the nutritional requirements of the species studied and proper development of anatomical structures. Fertilization with seaweed is beneficial to the development of banana cv. Prata-Anã in the acclimatization in greenhouse. It is recommended the use of 6 ml L-1 Lithothamnium in the acclimatization of banana cv. Prata-Anã.